DDOS Attack Analysis on IoT Device for Smart Home Environment and A Proposed Detection Technique - Ibrahim, Mohd Izwan; Darus, Mohamad Yusof (Society of Visual Informatics, 2024)
This study is grounded in a comprehensive review of literature on smart homes and Distributed Denial of Service (DDoS) attacks. To evaluate the defensive capabilities of pfSense and Suricata, a simulated Slowloris DDoS attack was performed on a smart home network, both with and without these security measures. Data was collected for each attack instance, followed by an analysis of the attack's effectiveness and the botnets' responses to refine DDoS assault strategies targeting smart home networks. The results revealed that the network was highly vulnerable without defense mechanisms, collapsing under the attack. In contrast, implementing pfSense and Suricata enabled swift detection and mitigation, neutralizing the attack within 15 seconds. Further testing involved five different scenarios, each assessing the ability of these systems to detect and block DDoS attacks. In all cases, the attacks were identified within 60 seconds. Attackers varied HTTP headers to flood IP-based cameras with packets ranging from 500 to 3000. The findings highlight the significant vulnerability of IoT devices in smart homes to cyber threats. However, deploying pfSense and Suricata proved to be a practical approach for detecting and mitigating DDoS attacks. The research underscores the importance of selecting high-quality hardware, evaluating IoT security features, and adopting proactive security practices to bolster smart home security.